Selective ablation of biological tissue and single cells on a glass substrate by controlling the laser energy density of nanosecond 193 nm laser radiation. Issue 10 (2nd September 2019) - Van Acker, Thibaut; Van Malderen, Stijn J. M.; Colina-Vegas, Legna; Ramachandran, Ranjith K.; Vanhaecke, Frank
Abstract : This work demonstrates the ability of nanosecond 193 nm laser radiation to selectively ablate biological material on a glass substrate. Abstract : This paper describes the possibility of controlling and reducing the laser energy density of nanosecond 193 nm laser radiation in order to selectively ablate biological material from a glass substrate for LA-ICP-MS bioimaging applications. Atomic force microscopy and optical profilometry were used to study the shape of single-shot craters in dried gelatin droplets, ablated at low energy (<500 mJ cm −2 ). These craters were characterized by straight walls and a 'flat bottom'. Based on the ablated volume per pulse and corresponding ablation depth, the ablation threshold of the dried gelatin material was estimated at 44 mJ cm −2 by relying on the Beer model derived from the Beer–Lambert law. Three different glass substrates, i.e. a microscope slide and coverslip of soda–lime–silica (SLS) glass with a slightly different bulk elemental composition and a borosilicate glass coverslip, were ablated using laser energy densities ranging from 150–730 mJ cm −2 and typical instrument settings applied during LA-ICP-MS bioimaging. The signal intensity of 29 Si, a minor isotope of Si which is a major matrix component of the glass surface, was monitored as a measure of material removal and was used to estimate ablation thresholds for the three glass substrates at 262, 181 and 104 mJ cm −2, respectively. As a proof-of-concept, kidney tissue mounted onto a SLS glass microscope slide substrate and MDA-MB-231 tumor cells seeded on a SLS glass coverslip were selectively ablated by controlling the laser energy density to ensure soft ablation of the glass substrate, but provide hard ablation of the biological material.